QTL mapping of fruit quality traits in tetraploid kiwiberry (Actinidia arguta) - Wang, Ran; Bourke, Peter M.; Li, Sikai; Lin, Miaomiao; Sun, Leiming; Gu, Hong; Li, Yukuo; Visser, Richard G.F.; Qi, Xiujuan; Maliepaard, Chris; Fang, Jinbao (Horticultural plant journal, 2025)
Fruit quality traits play an important role in consumption of kiwiberry (Actinidia arguta). The genetic basis of fruit quality traits in this woody, perennial and dioecious fruit crop remains largely unknown. This study aimed to identify the underlying genetic basis of fruit quality traits in A. arguta, using a single nucleotide polymorphism (SNP) genetic linkage map previously developed in a tetraploid F1 population of ‘Ruby-3’ × ‘KuiLv-M’. The F1 population was phenotyped over three years (2020–2022) for fruit quality traits, including skin color, flesh color, fruit weight, fruit diameter, total soluble solids, fruit longitudinal diameter and fruit shape index. A total of nine QTLs were detected for five traits, explaining 10%–32% of the trait variation. For fruit color, the support interval of a major QTL on LG9 contained an MYB transcription factor MYB110, which was previously demonstrated to control color regulation in kiwifruit, thus suggesting that the MYB110 is the candidate gene for fruit color in kiwiberry. The linked marker for fruit color was validated in an F1 population and 25 kiwiberry cultivars. In conclusion, the knowledge obtained through the QTL mapping is applicable to improve the efficiency and cost-effectiveness in kiwiberry breeding.